DAMPAK SOSIAL EKONOMI KONVERSI LAHAN PERKEBUNAN KE KAWASAN WISATA: : Studi Kasus Pada Rumah Pohon Desa Waai Maluku Tengah - Sifra Huwae; Yulma Leleulya; Imel Salenussa; Rokia Sahupalla (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the driving factors behind the conversion of plantation land into a tourist area, the management strategies, and the resulting socio-economic impacts at the Rumah Pohon Ecotourism in Waai Village, Central Maluku. The research employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model. The results indicate that land conversion is driven by the desire for a more stable income compared to seasonal agricultural yields. The area's management implements the POAC (planning, organizing, actuating, controlling) management functions. Social impacts are evident in the shifts in livelihoods, increased interaction with tourists, and the empowerment of local communities. Economic impacts include increased income, the creation of employment opportunities, and the development of new business ventures. Nevertheless, land conversion requires ecotourism-based management to ensure that economic benefits remain balanced with environmental conservation.